Adaptation strategies for preparing for childbirth in the context of the pandemic: Roy's Theory - Letícia Pickler; Margarete Maria de Lima; Ariane Thaise Frello Roque; Laís Antunes Wilhelm; Felice Curcio; Dionara Guarda; Roberta Costa; Isadora Ferrante Boscoli de Oliveira Alves (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to understand the process of adapting to childbirth during the COVID-19 pandemic from the perspective of a group of pregnant women. Methods: a qualitative, descriptive-exploratory study was conducted with 23 women. Data were collected between October and December 2021 through documentation and semi-structured interviews, which were analyzed using Minayo's methodology and Roy's Adaptation Model. Results: various types of stimuli - focal, contextual, and residual - were identified as influencing childbirth preparation. The online group was essential for facilitating pregnant women's adaptation, offering significant support and generating positive feedback for childbirth preparation. Final Considerations: the importance of pregnant women's groups as a strategy for improving adaptation to childbirth was identified, underscoring the effectiveness of this support among professionals and participants, as well as among pregnant women. This support network strengthened preparation for childbirth during a challenging period like the pandemic.